1991
DOI: 10.1177/089686089101100304
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Characterization of Mesothelial Lipid Inclusions

Abstract: The nature of intracytoplasmic lipid inclusions found in cultured rabbit and rat peritoneal mesothelial cells was examined by ultrastructural and biochemical techniques. Transmission electron microscopy also demonstrated extracellular release of these lipid bodies. Differential fixation with tannic acid revealed 2 types of inclusions, lamellated (lamellar bodies) and nonlamellated (homogeneous). The lamellar bodies were found near or in the Golgi apparatus and on the cell surface where occasionally they were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This led Dobbie et al [2] to point out the similarity of composition to that of pulmonary surfactant, in which the major constituent is also phosphatidylcholine. It was shown that, in peritoneum, mesothelial cells are the source of these phospholipids in i o [3] and in itro [4] and that, similarly to alveolar type II cells, they display lamellar bodies in their cytoplasm and at their surface. Lamellar bodies have been shown in the lung to represent the storage and exocytosis form of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…This led Dobbie et al [2] to point out the similarity of composition to that of pulmonary surfactant, in which the major constituent is also phosphatidylcholine. It was shown that, in peritoneum, mesothelial cells are the source of these phospholipids in i o [3] and in itro [4] and that, similarly to alveolar type II cells, they display lamellar bodies in their cytoplasm and at their surface. Lamellar bodies have been shown in the lung to represent the storage and exocytosis form of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Mesothelial cells have a remarkable biosynthetic potential, illustrated by the production of numerous micropinocytotic vesicles that form larger fused vesicles and vacuoles (Baradi and Rao, 1976;Ettarh and Carr, 1996). The cells synthesize and actively extrude a phospholipid-rich surfactant that lubricates the internal organs (Di Paolo, 1989;Dobbie and Lloyd, 1989;Hills, 2000;Hjelle et al, 1991). Mesothelial cells also reduce friction by the expression of numerous microvilli that mobilize and facilitate surfactant distribution, from surfactant-filled lamellar bodies (Andrews and Porter, 1973).…”
Section: Serosal Membrane Structure and Functionmentioning
confidence: 99%